2015
DOI: 10.1103/physrevb.91.094423
|View full text |Cite
|
Sign up to set email alerts
|

Exchange magnon-polaritons in microwave cavities

Abstract: We formulate a scattering theory to study magnetic films in microwave cavities beyond the independent-spin and rotating-wave approximations of the Tavis-Cummings model. We demonstrate that strong coupling can be realized not only for the ferromagnetic resonance mode, but also for spin-wave resonances; the coupling strengths are mode dependent and decrease with increasing mode index. The strong-coupling regime can also be accessed electrically by spin pumping into a metal contact.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
181
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 206 publications
(187 citation statements)
references
References 41 publications
6
181
0
Order By: Relevance
“…The "magnon" refers to the collective excitation of spin systems. In paramagnetic spin ensembles in an applied magnetic field, the spins precess coherently in the presence of microwave radiation, creating hybridized states referred to as magnon-polaritons [6][7][8]. In the strong-coupling regime coherent energy exchange exceeds the dissipative loss of both subsystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "magnon" refers to the collective excitation of spin systems. In paramagnetic spin ensembles in an applied magnetic field, the spins precess coherently in the presence of microwave radiation, creating hybridized states referred to as magnon-polaritons [6][7][8]. In the strong-coupling regime coherent energy exchange exceeds the dissipative loss of both subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…(i) strong coupling (SC) when 0.01 < g/ω c 0.1, (ii) ultrastrong coupling (USC) [26] when g/ω c 0.1, (iii) or even deep strong coupling (DSC) g/ω c ≈ 1 [27]. Cao et al [8] adapted the TC model to ferromagnets by formulating a first-principles scattering theory of the coupled cavity-ferromagnet system based on the Maxwell and the Landau-Lifshitz-Gilbert equation including the exchange interaction. A effectively onedimensional system of a thin film with in-plane magnetization in a planar cavity was solved exactly in the linear regime, exposing, for example, strong coupling to standing spin waves.…”
Section: Introductionmentioning
confidence: 99%
“…For example, CMP effect has recently been observed by setting miligrams of magnetic nano-particles inside a special circular waveguide cavity 11 , where the CMP coupling can be analyzed in the simple 1D configuration by using either the straightforward transfer matrix method 11 , or equivalently, the 1D scattering theory 12 . It is found that the CMP coupling enables quantifying the complex permeability of magnetic nanoparticles with high sensitivity, which was an outstanding challenge for the biomedical applications of magnetic nanoparticles 11 .…”
mentioning
confidence: 99%
“…Together, these latter parameters determine the coupling features of the system that can be configured from weak (K/α <1 and K/β <1) to strong coupling regime (K/α >1 and k/β >1). K can be tuned with (i) the volume of YIG 14,16 , (ii) the volume of the cavity 24 , and (iii) the magnitude of the microwave magnetic field 3,16 . Control of the coupling regime has been already demonstrated 7,25 by tuning the cavity losses β.…”
Section: B Thermal Controlmentioning
confidence: 99%
“…More recently, research groups 6-8 have developed an electrical method to detect magnons coupled with photons. This method has been established by placing a hybrid YIG/platinum (Pt) system into a microwave cavity, showing distinct features not seen in any previous spin pumping experiment but already predicted by Cao et al 14 . These later studies have been realized in a 3D cavity (with high Q factor), but insertion of an hybrid stack including a highly electrical conductor such as platinum has been reported to induce a drastic enhancement of the intrinsic loss rate.…”
Section: Introductionmentioning
confidence: 99%